A Numerical Model of Joule Heating in Piezoresistive Pressure Sensors - Abdelaziz Beddiaf; Fouad Kerrour; Salah Kemouche (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Thermal drift caused by Joule heating in piezoresistive pressure sensors affects greatly the results in the shift of the offset voltage of the such sensors. The study of the thermal behavior of these sensors is essential to define the parameters that cause the output characteristic drift. The impact of Joule heating in a pressure sensor has been studied. The study involves the solution of  heat transfer equation considering  the conduction in Cartesian coordinates for the transient regime using Finite Difference Method. We determine how the temperature affects the sensor during the applying a supply voltage. For this, the temperature rise generated by Joule heating in piezoresistors has been calculated for  different geometrical parameters of the sensor as well as for different operating time. It is observed that Joule heating leads to important rise temperature in the piezoresistor and, hence, causes drift in the output voltage variations in a  sensor during its operated in a prolonged time. This paper put emphasis on the geometric influence parameters on these characteristics to optimize the sensor performance. The optimization of geometric parameters of sensor allows us to reducing the internal heating effect. Results showed also that low bias voltage should be applied for reducing Joule heating.